The Contents and Features of Dispute Settlement under US-Jordan FTA: An Appraisal - Bashar H. Malkawi (Manchester Journal of International Economic Law, 2018)
The following discussion analyzes the dispute settlement mechanism provided for by the US-JO FTA. The article begins in section II with a brief introduction on the functioning of FTAs. Section III highlights the importance of including dispute resolution provisions in FTAs. Section IV analyzes the controlling procedure with respect to disputes includes: the Joint Committee of the FTA; standard of review; establishment and composition of panels; application and range of resolutions for disputes; panel report; transparency; forum shopping; the effect of rulings or recommendations; and implementation issues. Section V discusses the special dispute settlement rules for labor and environmental disputes. Section VI assesses the use of dispute resolution mechanism under the US-JO FTA. The article concludes by proposing improvements to the US-JO FTA dispute resolution mechanism and additions to its existing provisions.
Keywords: F10; F19; 330; International economic law; Trade agreements; Dispute settlement; WTO; NAFTA; Arab countries